Abnormalities of the Small Bowel in Chronic Non-Infective Diarrhea: A Histopathological Study - Marcellus Simadibrata Kolopaking; Vera Yuwono; Ari Fahrial Syam; FJW Ten Kate; GNJ Tytgat; Daldiyono Daldiyono; L A Lesmana; Nurul Akbar; Chudahman Manan; Iwan Ariawan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2003)
Background: The incidence of chronic non-infectious diarrhea cases is increasing in line with the developments of medical technology and science. The objective of this study was to uncover the histopathologic abnormalities of the small bowel in cases of chronic non-infectious diarrhea. Methods: All chronic non-infectious diarrhea patients in Cipto Mangunkusumo Hospital from 1996 until 2000 were included in this study. For the control group, we used 37 endoscopically-normal patients with functional dyspepia with the same characteristics (sex and age). All of the patients underwent gastroduodeno-jejunoscopic and ileocolonoscopic examinations. Patients with infection were excluded from this study. Biopsies were taken from the duodenal bulb, descending duodenum, jejunum near the Treitz ligament, terminal ileum, and colon. Histopathological tests were performed on all of the biopsies. Result: Histopathological examination was carried out on 31 patients and 37 control patients. In the duodenal bulb, the width of villi, lymphocyte infiltration, eosinophil infiltration, stage of inflammation, and polymorphonuclear cells infiltration were all lower in the chronic non-infectious diarrhea group than in the control group (p 0.01). In the descending part of duodenum and jejunum, lymphocyte infiltration, the stage of inflammation, and polymorphonuclear cell infiltration were found to be higher in the chronic non-infectious diarrhea group than in the control group (p 0.01). Within the terminal ileum, lymphocyte infiltration, the stage of inflammation and lymphoid follicle hyperplasia were found to be higher in the chronic non-infectious diarrhea group than in the control group (p 0.01). Conclusion: Histopathologically, increased lymphocyte infiltration, inflammation and lymphoid follicle hyperplasia were discovered in specified areas of small intestine in chronic non-infectious diarrhea patients. Keywords: Histopathological examination, chronic non-infectious diarrhea, lymphocyte infiltration, mucosal inflammation, lymphoid follicle hyperplasia